Limitations and prospects of sulfate-radical based advanced oxidation processes. Issue 4 (August 2020) - Duan, Xiaodi; Yang, Shanshan; Wacławek, Stanisław; Fang, Guodong; Xiao, Ruiyang; Dionysiou, Dionysios D.
Abstract: In recent years, there has been growing interest on the application of advanced oxidation processes (AOPs) based on sulfate radical in the elimination of organic contaminants. In such processes, sulfate radical is typically generated from the activation of peroxymonosulfate (PMS) or peroxydisulfate (PDS). In this paper, generation of sulfate radical by various methods and mechanism of activation processes for PMS or PDS were discussed. Moreover, certain applications of sulfate radical-based AOPs in wastewater, groundwater, and soil remediation were also summarized. More strategies, such as developing stable and highly efficient metal oxide activators, fabricating efficient carbonaceous-based materials, and combining with other treatment technologies, should be considered in further applications of sulfate radical-based advanced oxidation processes (SR-AOPs). In addition, more attention should be paid to elucidate the underlying mechanisms by coupling experimental analysis with theoretical models. The generation of toxic byproducts, high level of sulfate ion, and complex quenching reactions are pointed out as main limitations. Finally, further studies on mechanistic aspects of the chemistry involved and evaluation of the potential for on-site applications are desired to further explore implementation of such SR-AOPs.